Value Relevance of Earnings and Book Value: Impact of Earnings Management and Family-Owned Firms - Ratnaningrum Ratnaningrum; Rahmawati Rahmawati; Djuminah Djuminah; Ari Kuncara Widagdo (Indonesian Journal of Sustainability Accounting and Management, 2022)
The purpose of this study is to investigate whether family-owned firms and earnings management as a result of financial distress affect the value relevance of earnings and book value. The study is based on companies listed on the Indonesia Stock Exchange (IDX). An unbalanced panel dataset of 592 firms trading in the IDX from 2012 to 2017 was used to test the price model. Results reveal that owing to high financial distress, earnings management through an income-increasing strategy was opportunistically conducted. Moreover, earnings management (as opposed to financial transparency, which is a principle of sustainability) decreases the value relevance of earnings. Due to high financial distress, there is a trade-off between the value of earnings and relevance of book value in earnings management. Further, results demonstrate that the value relevance of earnings in family-owned firms is higher than in nonfamily-owned firms in Indonesia. It indicates that earnings management due to high financial distress contributes to the alignment effect on family firms.